Aiding democracy? doners and civil society in South Africa - Hearn, Julie (2000)
During the 1990s the North has increasingly used a new tool, political aid, to influence its relations with the South. More commonly known as `democracy assistance', political aid is targeted at governmental structures such as parliament, the judiciary and local government, as well as civil society organisation, with the aim of strengthening the institutions and culture of liberal democracy. However, despite its increasing deployment, the shape and extent of foreign political aid in individual countries in the South remain largely undocumented. This article shows the importance of political aid in South Africa since the pivotal elections of 1994. It then critically examines the role assigned to civil society by donors within the `democratisation' process. Unlike most writers on the new political aid regime, who are often both its chroniclers and mandarins, this author questions the emancipatory potential of the kind of democracy being `helped along' by democracy assistance. - Reproduced
Keywords: Democracy - South Africa; Civil society - South Africa; South Africa - Politics and government; Politics and government